2016
DOI: 10.1371/journal.pone.0166340
|View full text |Cite|
|
Sign up to set email alerts
|

Arnica montana Stimulates Extracellular Matrix Gene Expression in a Macrophage Cell Line Differentiated to Wound-Healing Phenotype

Abstract: Arnica montana (Arnica m.) is used for its purported anti-inflammatory and tissue healing actions after trauma, bruises, or tissue injuries, but its cellular and molecular mechanisms are largely unknown. This work tested Arnica m. effects on gene expression using an in vitro model of macrophages polarized towards a “wound-healing” phenotype. The monocyte-macrophage human THP-1 cell line was cultured and differentiated with phorbol-myristate acetate and Interleukin-4, then exposed for 24h to Arnica m. centesima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 78 publications
2
62
1
Order By: Relevance
“…Arnica ( A. montana ) is an herbaceous perennial plant from Europe which is cultivated in several places, that is, USA, and it has been used in wound treatment since the 16th century due to its anti‐inflammatory, antimicrobial, and healing properties . The active compounds in Arnica are sesquiterpene lactones, thymol derivatives, flavonoids, acid polysaccharides, and their glycol conjugates and the effective anti‐inflammatory compounds are helenalin and sesquiterpene lactones . Arnica gel has been effective in Wistar rats' wound healing and Arnica‐Stinging nettle extract accelerated human wound healing …”
Section: Introductionmentioning
confidence: 99%
“…Arnica ( A. montana ) is an herbaceous perennial plant from Europe which is cultivated in several places, that is, USA, and it has been used in wound treatment since the 16th century due to its anti‐inflammatory, antimicrobial, and healing properties . The active compounds in Arnica are sesquiterpene lactones, thymol derivatives, flavonoids, acid polysaccharides, and their glycol conjugates and the effective anti‐inflammatory compounds are helenalin and sesquiterpene lactones . Arnica gel has been effective in Wistar rats' wound healing and Arnica‐Stinging nettle extract accelerated human wound healing …”
Section: Introductionmentioning
confidence: 99%
“…Fibrillin 2 and MACF1 genes were slightly stimulated, but the absolute values of MNE were very low and the changes were not statistically significant. CR1 gene was omitted from the RT-qPCR analysis because in RNA-seq results 12 its expression level was extremely low (between 1 and 2.5 reads per kilobase million).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Investigations of its mechanisms of action have focused on inflammatory pathways, [5][6][7][8][9][10][11] but little is known about its possible action on the stages of tissue formation and renovation. In our laboratory, [11][12][13][14] we used the THP-1 human cell line, commonly employed to explore the function and regulation of monocytes and macrophages, 15 which are involved in inflammation and wound healing. 16 One of these articles 12 was recently retracted by the journal PlosONE due to criticisms raised about the concentration of Arnica m. used in the experiments and about the purported small gene expression changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recent research has shown the effectiveness of Arnica montana given in homeopathic potencies in many clinical conditions, 6 and also in the gene expression. 7 …”
mentioning
confidence: 99%